Relation of Lymphangiogenic Factor Vascular Endothelial Growth Factor-D to Elevated Pulmonary Artery Wedge Pressure - Houston, Brian A.; Tedford, Ryan J.; Baxley, Renee L.; Sykes, Brandon; Powers, Eric R.; Nielsen, Christopher D.; Steinberg, Daniel H.; Maran, Anbukarasi; Fernandes, Valerian L.C.; Todoran, Thomas; Jones, Jeffrey A.; Zile, Michael R. (The American journal of cardiology, 2019)
Lymphatic flow is augmented in states of chronic heart failure (cHF). However, the biological mechanism driving increased lymphatic flow capacity (lymphangiogenesis) in cHF is unknown. Recent studies have indicated that vascular endothelial growth factors (VEGF-A, -C, and -D) are involved in lymphangiogenesis. This study examined the association between VEGF-A, -C, and -D levels, invasively measured hemodynamics, and heart failure symptoms. Subjects who underwent clinically indicated right heart catheterization at Medical University of South Carolina between 12/2016 and 7/2018 were eligible for inclusion. These subjects underwent clinical assessment of cHF severity (including 6MWT and KCCQ), hemodynamic assessment with right heart catheterization, laboratory studies including B-type natriuretic peptide, and concomitant measurement of VEGF-A, -C, and -D. Fifty-six patients were included for analysis. Subjects with elevated pulmonary artery wedge pressure (PAWP) had significantly higher VEGF-D levels (263 ± 415 pg/ml vs 65 ± 101 pg/ml; p = 0.02). PAWP was not associated with VEGF-A or VEGF-C levels. When stratified by VEGF-D, subjects with elevated VEGF-D had clinical and hemodynamic characteristics associated with worse HF severity (lower ejection fraction, higher b-type natriuretic peptide, higher PAWP, lower cardiac output), but were not more symptomatic by Kansas City Cardiomyopathy Questionnaire scores and had similar 6-minute walk test distance compared with subjects with lower VEGF-D. Subjects with an elevated VEGF-D were more likely to have a diagnosis of heart failure for >3 years. In conclusion, VEGF-D is associated with elevated PAWP in cHF, and elevated VEGF-D may mitigate cHF symptoms.